International policy coordination for financial regime stability under cross-border externalities - Park, Sungmin; Kim, Young-Han (Journal of Banking & Finance, 2018)
This paper examines the conditions for effective coordination in financial regulatory policy when banks are politically influential, considering cross-border externalities arising from multinational banking operation. We demonstrate that when banks are inefficient with high loan monitoring costs, regulatory effort is a strategic substitute so that each country's regulator tends to exert lower effort free-riding that of the other countries’ regulator. On the other hand, when banks are efficient with lower monitoring costs, regulatory effort is a strategic complement and regulators have lower incentives to free-ride. However, regulators face multiple equilibria and thus financial instability if each of them responds in an overly sensitive manner to another's strategy. In this case, introducing informational barriers can refine multiple equilibria into a unique equilibrium. The results suggest that cooperative financial policy coordination mechanism is more likely to be sustained among countries whose banking sectors’ political influence on regulators is smaller and more homogeneous.